Source of plastic contamination of the rivers ending to the Gorgan Bay, southeast of the Caspian Sea, Iran - Gholizadeh, Mohammad; Hedayati, Aliakbar; Pouladi, Mojtaba; Sundaramanickam, Arumugam (Frontiers in Marine Science, 2024)
The widespread presence of microplastics (MPs) in freshwater systems as an emerging environmental pollutant has caused a global environmental problem. The present study investigates the distribution and abundance of source pathway and abundance of microplastics in surface sediment samples from rivers discharging into the Gorgan Bay, southeast of the Caspian Sea. A total of 57 surface sediment samples were taken from 19 stations to investigate the potential hot spots of pollution in the four rivers leading to the Gorgan Bay. The average level of microplastics was 333 ± 268 particles/kg. The highest amount is in the estuary of the Qarasu River (1080 ± 380 particles/kg) due to the accumulation of fishing, boating and tourism activities and the lowest amount in the forest area (80 ± 19 particles/kg) in the Klak River. The most common type of microplastic was fiber (68%). Microplastic pollution in the studied rivers is mostly black and gray (75.39%), and about 53% of them were sized less than 1000 μm. Spectroscopic analysis (Fourier Transform Infrared (FT-IR) of the MP showed that 37% were polyethylene, polyethylene (37%) and polypropylene (27%) were the dominating groups. The sediments’ size was significantly correlated (p>0.05) with the presence of microplastics. Sediments with a coarse grain (sand) demonstrated a great potential to store microplastics. The results of this study can be used for the management and protection policies of Gorgan Bay.